Process options for the treatment of humic rich waters - Fearing, David Andrew (Cranfield University, 2004)
Seasonal periods of high rainfall have led to difficulties in removing sufficient natural organic matter (NOM) to meet trihalomethane (THM) standards, and hence better or alternative treatments are required. Typically bulk water parameters such as dissolved organic carbon (DOC) and UV absorbance at 254nm (UV254) are used to optimise treatment processes. Here the isolated fraction character and molecular weight (MW) distribution was used in conjunction with bulk water parameters to tailor process options for the treatment of humic rich waters. Three options for the removal of NOM were proposed. A staged coagulation based on the optimisation of isolated fractions. The results showed that although no significant reduction in DOC or UV254 was observed filter breakthrough was significantly reduced. Secondly a novel magnetic ion exchange process (MIEX®) for the removal of NOM was evaluated. The results showed that a combination of MIEX® and ferric reduced the THM formation potential (THMFP) by more than 50% and lower MW compounds that are known to be untreated by conventional coagulation were reduced. This option was also shown to be the most robust option for the treatment of waters with differing quality caused by seasonal changes and different catchments. Finally the addition of a range of adsorbents including carbons, hydroxides and clays to both the raw water and the isolated low MW fractions showed that an increase in DOC and UV254 removal was achievable. This was proposed as a post coagulation option during times of high organic loading. All processes provide viable options for the treatment of humic rich waters during times when current processes are being challenged and having difficulty meeting THM standards.
Keywords: Water treatment; Natural organic matter; Trihalomethane